Effects of mentoring on self-reflection and competence in final year medical students’ internal medicine rotation - Heckmann, Markus B.; Mages, Christine; Finke, Daniel; Reich, Christoph; Haney, Ailís Ceara; Riedel, Caroline; Bugaj, Till Johannes; Frey, Norbert; Rahm, Ann-Kathrin (PLOS ONE, 2025)
Background Final year medical students (FYMS) in Germany transfer theoretical knowledge to clinical practice. However, there is a deficiency in structured guidance and feedback and self-reflective practices are often neglected. This study aims to investigate the impact of three mentoring strategies on cultivating self-reflection and introspection in FYMS and to assess competence during routine activities. Methods Final year medical students (n = 46) completing a mandatory internal medicine rotation at Heidelberg University Hospital were randomized to either passive mentoring or active mentoring (split into structured and unstructured sessions). Across an 8-week rotation, we assessed the influence of mentoring styles on self-reflection and introspection (SRIS) at the beginning and at the end of the rotation. Changes in SRIS were compared by Mann Whitney U tests. Translated, adapted and newly generated questionnaires were analysed calculating cronbach’s alpha and optimized using an item-drop analysis. Results Key findings include: a general reluctance to initiate mentor-mentee relationships (1 out of 15 in the passive group sought meetings, p < 0.0001), a propensity for FYMS to undervalue their competence compared to external evaluations (3.6 vs. 4.5 p < 0.0001), a tendency for female FYMS to have higher perceived competence (PCS) than males, with means of 3.8 vs. 3.3 (p = 0.0021), and a measurable improvement in introspection (SRIS-IN) across all participants by the program’s end, regardless of the mentoring style received (median change on scale: 0.25, p = 0.0016). However, the mentoring intervention itself revealed no significant impact on self-reflection. Conclusions Active mentoring had little to no effect on self-reflection and insight of final year medical students in Germany in the setting of an 8-week rotation. Interventional learning studies were well accepted, and participation rate was high. However, form completion rates were low. Future studies should focus on increasing form completion rates through additional incentives.